Automatic Compact Coffee Maker Using Temperature and Weight Sensors With Arduino Microcontroller - Soraya Norma Mustika; Narendra Handaryan Yudhistira; Eko Noerhayati; Achmad Hamdan (Journal of Engineering, Electrical and Informatics, 2024)
In carrying out the process of grounding coffee manually, some people still rely on manual tools and based solely on the help of human hands, ineffectiveness often occurs. If the coffee beans are processed manually, the process will take quite a long time or if the coffee beans are processed manually themselves, it will produce less than perfect coffee bean powder. It is difficult to regulate the level of maturity or detect the right temperature of the coffee beans to produce the right coffee taste. It also requires a roasting process to a grinding process to turn the coffee beans into coffee powder with the right taste. Based on the problems above, the aim of this research is to simplify the process of converting coffee beans into coffee powder automatically and easily. In carrying out the roasting process to the process of refining the coffee beans, you need to pay attention to three aspects, namely the hot temperature during the roasting process, and determining the weight of the coffee beans when the coffee beans are finished going through the roasting process with a capacity of 100 g. In this research, to control and monitor the temperature and weight of coffee beans using an arduino microcontroller.